2001
DOI: 10.1097/00007632-200111150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Cervical Pedicle Screw Placement Using the Funnel Technique

Abstract: Axial computed tomography is necessary for the preoperative planning. Because of the small diameter and steep angulation of cervical pedicles, every spine surgeon who intends to use pedicle screws should first master the technique on cadavers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
118
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 22 publications
2
118
0
Order By: Relevance
“…Fixation with pedicle screws is particularly useful for cervical spine stabilisation, as it enables application of a distraction force to the injured cervical spinal segment. [20][21][22][23][24][25][26] In our study, there was no discontinuity of the posterior vertebral body (on magnetic resonance imaging), indicating that ligamentous continuity of the injured disc level was preserved, and no patient experienced postoperative neurological deterioration. Cervical transpedicular fixation can safely reduce disc herniation and stabilise the cervical spine in one stage, precluding the need for anterior decompression.…”
Section: Discussionmentioning
confidence: 84%
“…Fixation with pedicle screws is particularly useful for cervical spine stabilisation, as it enables application of a distraction force to the injured cervical spinal segment. [20][21][22][23][24][25][26] In our study, there was no discontinuity of the posterior vertebral body (on magnetic resonance imaging), indicating that ligamentous continuity of the injured disc level was preserved, and no patient experienced postoperative neurological deterioration. Cervical transpedicular fixation can safely reduce disc herniation and stabilise the cervical spine in one stage, precluding the need for anterior decompression.…”
Section: Discussionmentioning
confidence: 84%
“…Irrespective of all of the favorable properties of pCPSs, investigators have called attention to the liberal use of pCPSs because of the possibility of iatrogenic neurovascular injuries [19]. Although placement of pCPSs poses a potential risk to nearby neurovascular structures, standards are established, and several studies have demonstrated a significantly decreased risk for complications through the implementation of navigation tools and surgical training, which increases accuracy [4,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, lateral mass screws are not without their risks [25], and pedicle screw placement in the lumbar spine has a documented perforation rate of over 5% [8] despite the larger diameter of the pedicles. Documented cervical pedicle perforation rates vary from 4 to 87.5% [2,4,5,11,16,17,24,29], with cadaveric studies reporting a higher incidence than comparable clinical experiments. However, throughout the literature there is a distinction between 'minor' and 'critical' perforation rates, with the former unlikely to be of clinical significance.…”
Section: Discussionmentioning
confidence: 99%